2008
DOI: 10.1016/j.eurpsy.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

CSF monoamine metabolites and neuropeptides in depressed patients before and after electroconvulsive therapy

Abstract: Antidepressant drugs affect monoamines and neuropeptides in human cerebrospinal fluid (CSF) and in rodent brain. The purpose of this study was to investigate if also electroconvulsive therapy (ECT) affects these compounds in a similar manner in the CSF of depressed patients. Homovanillic acid (HVA), 5-hydroxyindoleacetic acid (5-HIAA), and corticotropin-releasing hormone (CRH)-like immunoreactivity (-LI) and neuropeptide Y (NPY)-LI were determined in CSF in six drug resistant patients with major depression. Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0
5

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 37 publications
(56 reference statements)
4
41
0
5
Order By: Relevance
“…Thus, NPY may modulate a variety of behaviors, including conditioned fear (Gutman et al, 2008) and human stress reactivity (Mickey et al, 2011;Witt et al, 2011) via Epac pathways and serve as a critical element in the pathophysiology of depression, PTSD, and other neuropsychiatric disorders. Indeed, several studies implicate changes in NPY levels in depression (Domschke et al, 2010;Nikisch and Mathe, 2008), anxiety disorders (Amstadter et al, 2010;Wu et al, 2011), and PTSD (Rasmusson et al, 2010;Sah et al, 2009). …”
Section: Implications Of Epac As a Novel Intracellular Signaltransducmentioning
confidence: 99%
“…Thus, NPY may modulate a variety of behaviors, including conditioned fear (Gutman et al, 2008) and human stress reactivity (Mickey et al, 2011;Witt et al, 2011) via Epac pathways and serve as a critical element in the pathophysiology of depression, PTSD, and other neuropsychiatric disorders. Indeed, several studies implicate changes in NPY levels in depression (Domschke et al, 2010;Nikisch and Mathe, 2008), anxiety disorders (Amstadter et al, 2010;Wu et al, 2011), and PTSD (Rasmusson et al, 2010;Sah et al, 2009). …”
Section: Implications Of Epac As a Novel Intracellular Signaltransducmentioning
confidence: 99%
“…[15][16][17][18][19][20] In addition, it has been reported that the reduced hippocampal NPY levels in animal models of depression were restored by treatment with antidepressants, 12,15,21) electroconvulsive stimuli, [16][17][18][19] and running. 22) Moreover, additional evidence has shown that NPY per se exhibits antidepressantlike activity via the Y1 receptor [23][24][25][26] and promotes the proliferation of hippocampal neural progenitor cells.27-31) These findings suggest that the upregulation of hippocampal cell proliferation and neurogenesis, the downregulation of which is inversely associated with the pathology of depression, 32,33) could be required for NPY-induced antidepressant-like effects.In clinical studies, some reports have suggested that NPY levels in the cerebrospinal fluid are decreased in patients with major depression [34][35][36][37] and that the NPY levels are improved by electroconvulsive therapy 38) and treatment with an antidepressant. 39) Improvement in the dysfunction of the NPY system might alleviate some afflictions in patients with major depression.…”
mentioning
confidence: 99%
“…In clinical studies, some reports have suggested that NPY levels in the cerebrospinal fluid are decreased in patients with major depression [34][35][36][37] and that the NPY levels are improved by electroconvulsive therapy 38) and treatment with an antidepressant. 39) Improvement in the dysfunction of the NPY system might alleviate some afflictions in patients with major depression.…”
mentioning
confidence: 99%
“…Pese a lo ampliamente usada en psiquiatría y a la mejoría de las técnicas y la práctica clínica de la TEC, los mecanismos por los cuales produce su efecto terapéutico aún son desconocidos. Entre las hipótesis existentes hay quienes afirman que habría cierta influencia sobre el sistema neurotransmisor, ya que se ha demostrado un aumento en la liberación de neurotransmisores de monoamina, particularmente dopamina y serotonina tanto en animales como en humanos 1,2 . Otra hipótesis se basa en el efecto que produce la TEC en el eje hipotálamo-hipófisis-suprarrenal, ya que se ha demostrado que las convulsiones repetidas aumentan la producción y liberación de un péptido hipotalámico que se relaciona con la mantención del estado de ánimo 3 .…”
Section: ¿Qué Es La Tec?unclassified